Stabilizing black-phase formamidinium perovskite formation at room temperature and high humidity - Hui, Wei; Chao, Lingfeng; Lu, Hui; Xia, Fei; Wei, Qi; Su, Zhenhuang; Niu, Tingting; Tao, Lei; Du, Bin; Li, Deli; Wang, Yue; Dong, He; et al. (Science (American Association for the Advancement of Science), 2021)
Although methods have been developed that create the photoactive black perovskite phase of formamidinium lead iodide (α-FAPbI 3 ), these routes are temperature and humidity sensitive and less compatible with large-scale solar cell production. Hui et al. report an alternative route in which vertically aligned lead iodide thin films are grown from the ionic liquid methylamine formate. Nanoscale channels in the films lower the barrier to permeation of formamidinium iodide and enable transformation to α-FAPbI 3 , even at high humidity and room temperature. Solar cells made with these films have power conversion efficiencies as high as 24.1% that display high stability. Science , this issue p. 1359 Vertically aligned lead iodide thin films grown from an ionic liquid enable ambient growth of black-phase perovskite. The stabilization of black-phase formamidinium lead iodide (α-FAPbI 3 ) perovskite under various environmental conditions is considered necessary for solar cells. However, challenges remain regarding the temperature sensitivity of α-FAPbI 3 and the requirements for strict humidity control in its processing. Here we report the synthesis of stable α-FAPbI 3 , regardless of humidity and temperature, based on a vertically aligned lead iodide thin film grown from an ionic liquid, methylamine formate. The vertically grown structure has numerous nanometer-scale ion channels that facilitate the permeation of formamidinium iodide into the lead iodide thin films for fast and robust transformation to α-FAPbI 3 . A solar cell with a power-conversion efficiency of 24.1% was achieved. The unencapsulated cells retain 80 and 90% of their initial efficiencies for 500 hours at 85°C and continuous light stress, respectively.